Isolasi dan Identifikasi Bakteri Heterotrofik di Perairan Pantai Paris Tigaras Kabupaten Simalungun - Lestari, Sri Winda; Mayasari, Ulfayani; Rasyidah, Rasyidah (KLOROFIL: Jurnal Ilmu Biologi dan Terapan, 2023)
Heterotrophic bacteria are bacteria that have a role as decomposers of waste in the form of carbon compounds such as leaves, wood from plants and animal carcasses which will produce minerals as nutrients, so that waste does not accumulate on the Paris coast. The purpose of this research was to determine the types of bacterial isolates and characteristic of heterotrophic from water Paris beach. Bacterial isolation was carried out using the spread method on nutrient agar medium. The result of isolation was 10 bacteria isolates which were then purified and observation of macroscopic morphology. The result showed that bacterial isolates SP2I1, SP4I4, SP1I7 were heterotrophic. Bacterial isolates SP2I1, SP4I4 was gram–positive with rod-shapes cells, while bacteria isolates SP1I7 was gram-negative (rod-shaped cells). Based the result of biochemical tests, morpjology observations, the bacterial isolates SP2I1, SP4I4 belongs to the genus Bacillus and isolates SP1I7 belongs to the genus Enterobacter.